Evaluation of the thermal properties of PLA/SEBS blends with moringa subjected to degradation in a marine environment (Research, Society and Development, 2021)
In this work, the influence of the SEBS and Moringa Oleifera content on the thermal properties PLA/SEBS blends and of two biocomposites based on two of these blends was investigated. Two PLA/SEBS blends (90/10 and 70/30), two PLA/SEBS/MO biocomposites (90/10/1 and 70/30/1), and a PLA/MO (100/1) biocomposite, were prepared by melt mixing in an open die extruder. The samples for biodegradation were obtained by hot pressing, being subsequently inserted in a simulated marine environment. Degradation development has been evaluated through mass variation, thermogravimetry, and differential scanning calorimetry. It was observed an increase in crystallinity of all the evaluated compositions, and a reduction of the thermal stability after the exposure to the marine environment for prolonged periods This higher crystallinity may be related to the consumption of amorphous regions and the lower thermal stability is linked to the hydrolytic degradation of PLA, due to the water absorbed by the moringa powder. The evaluation of the mass variation showed that the mixtures with SEBS and Moringa, presented a degradation rate equivalent or lower to that reported for neat PLA.